Portuguese adaptation of the S3-non-invasive ventilation (S3-NIV) questionnaire for home mechanically ventilated patients - Ribeiro, C (2020)
Short, valid and easy to use tools are needed to monitor non-invasive ventilation in clinical practice and for organization of home mechanical ventilation services. The aim of this study was to develop a professional translation and cultural adaptation of the Portuguese S3 non-invasive ventilation questionnaire. 234 stable patients (128 male patients, 53.8%) with a mean age of 69.3 years under long-term home non-invasive ventilation were recruited from a single-center outpatient clinic. The most frequent diagnostic groups were obesity hypoventilation syndrome, chronic obstructive pulmonary disease and restrictive chest wall disorders. The Portuguese version of the questionnaire was obtained using translation back-translation process with two professional translators. Internal consistency for the total score was good (Cronbach’s α coefficient of 0.76) as well as for the “respiratory symptoms” and the “sleep and side effects” domains (Cronbach’s α coefficient = 0.68 and Cronbach’s α coefficient = 0.72, respectively). An exploratory factor analysis was performed leading to an explained variance of 54.6%, and resulted in 3 components. The Portuguese version of the S3-NIV questionnaire is a simple and valid tool for the routine clinical assessment of patients receiving home NIV.